2021
DOI: 10.1101/gad.347989.120
|View full text |Cite
|
Sign up to set email alerts
|

Molecular principles of Piwi-mediated cotranscriptional silencing through the dimeric SFiNX complex

Abstract: Nuclear Argonaute proteins, guided by their bound small RNAs to nascent target transcripts, mediate cotranscriptional silencing of transposons and repetitive genomic loci through heterochromatin formation. The molecular mechanisms involved in this process are incompletely understood. Here, we show that the SFiNX complex, a silencing mediator downstream from nuclear Piwi-piRNA complexes in Drosophila, facilitates cotranscriptional silencing as a homodimer. The dynein light chain protein Cut up/LC8 mediates SFiN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 74 publications
2
17
0
Order By: Relevance
“…Artificial dimerization of a panx mutant that could no longer interact with Dlc (using the same GCN4 leucine zipper) restored the function of panx (Eastwood et al, 2021;Schnabl et al, 2021). Similar to our findings, the rescue of certain panx mutant phenotypes was incomplete (Schnabl et al, 2021).…”
Section: The Role Of Egl Dimerizationsupporting
confidence: 87%
See 1 more Smart Citation
“…Artificial dimerization of a panx mutant that could no longer interact with Dlc (using the same GCN4 leucine zipper) restored the function of panx (Eastwood et al, 2021;Schnabl et al, 2021). Similar to our findings, the rescue of certain panx mutant phenotypes was incomplete (Schnabl et al, 2021).…”
Section: The Role Of Egl Dimerizationsupporting
confidence: 87%
“…Recently, Panoramix (Panx), a protein that functions in the piRNA pathway was also shown to dimerize in a Dlc-dependent manner (Eastwood et al, 2021;Schnabl et al, 2021). Artificial dimerization of a panx mutant that could no longer interact with Dlc (using the same GCN4 leucine zipper) restored the function of panx (Eastwood et al, 2021;Schnabl et al, 2021).…”
Section: The Role Of Egl Dimerizationmentioning
confidence: 99%
“…(b) Hypothetical model showing the condensation of multiple Piwi–piRNA silencing complexes. Possible formation of LLPS is suggested in recent studies (Eastwood et al., 2021; Schnabl et al., 2021)…”
Section: The Pirna‐guided Silencing Pathway In Drosophila Regulates Te‐inserted Genomic Regionsmentioning
confidence: 83%
“…Nxf2 associates with the nascent transcript of target TEs to form a silencing complex. Recent studies have suggested that Panx can further associate with Cut‐up/LC8 and form a dimerized structure, suggesting the possibility that the Piwi–piRNA silencing complex can form a liquid‐liquid phase separation (LLPS) (Eastwood et al., 2021; Schnabl et al., 2021) (Figure 4b). HP1a, which is recruited to H3K9me, and the linker histone H1 are further associated with the piRNA target regions to induce a stable heterochromatin structure (Huang et al., 2013; Iwasaki et al., 2016; Le Thomas et al., 2013; Rozhkov et al., 2013).…”
Section: The Pirna‐guided Silencing Pathway In Drosophila Regulates Te‐inserted Genomic Regionsmentioning
confidence: 99%
See 1 more Smart Citation